Swimming Activity as an Indicator of Seasonal Diapause in the Copepod Calanus finmarchicus - Grigor, Jordan J.; Freer, Jennifer J.; Tarling, Geraint A.; Cohen, Jonathan H.; Last, Kim S. (Frontiers in Marine Science, 2022)
Copepods dominate zooplankton biomass of the upper ocean, especially in the highly seasonal boreal and polar regions, for which specific life-cycle traits such as the accumulation of lipid reserves, migration into deep water and diapause are key adaptations. Understanding such traits is central to determining the energetic consequences of high latitude range shifts related to climate change and ultimately, biogeochemical models of carbon flow. Using the calanoid copepod Calanus finmarchicus, we explore a new indicator of diapause, swimming activity, and assess its relationship with respiration. Stage CV copepods were sampled in late summer from shallow (epipelagic) and deep (mesopelagic) water at both slope and basin locations within the Fram Strait at a time when the animals had entered diapause. Using high-throughput quantitative behaviour screening on ex-situ swimming activity, we found that irrespective of sampling station copepods from the mesopelagic show highly reduced activity (88.5 ± 3.4% reduction) when compared to those from the epipelagic with a clearly defined threshold between epi- and mesopelagic animals ( 5 beam breaks 30 min-1). Mesopelagic individuals were also larger (12.4 ± 8.8%) and had more lipid reserves (19.3 ± 2.2%) than epipelagic individuals. On average, copepods from the basin station exhibited respiration rates similar to overwintering rates observed elsewhere (1.23 ± 0.76 µg C d-1), while respiration rates of copepods from the shelf station were more consistent with active metabolism (2.46 ± 1.02 µg C d-1). Nevertheless, active and diapausing rates were observed in individuals from both stations at both epi- and mesopelagic depths. We suggest that rapid screening of activity may provide an early indicator of diapause before it becomes fully apparent and consistent in other physiological indicators. Ultimately, swimming activity may provide a useful tool to assess the putative endogenous and exogenous factors involved in diapause onset, provide a handle on the energetics of diapause, and input to biogeochemical carbon models on C. finmarchicus.